Heat Balance Calculation in Industrial Enterprises - Shaxboz, Komilov; Ilhom, Isomiddinov (Journal of Innovation in Education and Social Research, 2024)
The heat balance calculation in industrial enterprises is pivotal for optimizing energy consumption, enhancing production efficiency, and reducing operational costs. This paper discusses the fundamental principles of heat balance, the methodology for its calculation, and its application across various industries. The analysis incorporates numerical examples, highlights energy losses, and outlines practical strategies for improving energy efficiency.